PEMBERDAYAAN, KEPEMIMPINAN DAN KOMITMEN ORGANISASI: SEBUAH ANALISIS KONSEPTUAL - Ridwan Nurdin (Jurnal Manajemen Inovasi, 2018)
This article aims to review the concept of Empowerment associated with Leadership and Organizational Commitment. Empowerment is essentially a motivational process of individual experience to make the individual feel more empowered (enabled). Theoretically empowerment can be interpreted as giving responsibility and authority to someone or individual to make a decision. This article, using the method of library studies and descriptive analysis, reveals the concept of empowerment related to leadership and commitment within an organization. Keywords:Empowerment, Leadership, Organizational Commitment